TRANSPARANSI DALAM PELAKSANAAN BANTUAN LANGSUNG TUNAI (BLT) DANA DESA - Tioma Roniuli Hariandja; Nanang Tri Budiman (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2020)
Since May 2020, BLT DD has been implemented in Jember Regency, including Bangsalsari Village. However, in fact it’s couldn’t avoid a pros and cons, especially to recipients. So, it’s mean Bangsalsari must be respons and give right information public. Every regulation must referent to hierarchy of legislation, same as the BLT DD rules. However, we know law have the legal principles